Finite Element-Based Optimization of Cross-Section Area on 2D Truss Structure with 10-members and 12-members Using Nonlinear Programming Method - Nazaruddin - Nazaruddin; Feblil Huda; Hafizah Hafizah; Fatiya Fatiya (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
Designing a structure requires good planning to obtain optimal results. Some things that need to be considered in designing structures are the materials used, the dimensions of the structure, and others. By optimizing the dimensions of the structure, the use of materials can be minimized so that production costs can be reduced. The experiment requires additional cost and time. Therefore, finite element software can be used to design the structure optimally in compliance with the constraints set according to the requirements. Previous studies have carried out cross-section area optimization of structures with maximum allowable stress limits. In this research, the optimization of 2D truss cross-section area with maximum volume constraint is developed using MATLAB software with fmincon function. The structure is modelled in 2 shapes: a 2D truss with ten members and a 2D truss with twelve members. The optimum area is obtained from the simulation results, which are almost the same in both structures, while the lower stress value is obtained in the ten-member 2D truss structure. The maximum stress (tensile stress) on the 12-member 2D truss occurs on element 12 at 3484.28 psi, and then the minimum stress (compressive stress) occurs on elements 3, 4, 8, and 9 at -3472.10 psi. The maximum stress (tensile stress) on the 10-member 2D truss structure occurs in elements 1 and 9 at 3472.10 psi, and the minimum stress (compressive stress) occurs in element four at -3479.77 psi.